Molecular epidemiology of Microsporidia among HIV-positive and HIV-negative patients in the Limpopo province, South Africa - Amidou Samie; Rhulani Patricia Maluleke; Nicoline Tanih; Ali ElBakri (Journal of Infection in Developing Countries)
Introduction: Human microsporidiosis represents an important and rapidly emerging opportunistic disease. The present study investigated the prevalence of microsporidia among HIV positive and HIV negative patients with or without diarrhoea in Vhembe and Mopani Districts in the Limpopo Province.